Control of persistent photoconductivity in nanostructured InP through morphology design - Monaico, Ed; Postolache, V.; Borodin, Elijah; Ursaki, V. V.; Lupan, Oleg; Adelung, Rainer; Nielsch, Kornelius; Tiginyanu, I. M. (Semiconductor Science and Technology, 2015)
In this paper, we show that long-duration-photoconductivity decay (LDPCD) and persistent photoconductivity (PPC) in porous InP structures fabricated by anodic etching of bulk substrates can be controlled through the modification of the sample morphology. Particularly, the PPC inherent at low temperatures to porous InP layers with the thickness of skeleton walls comparable with pore diameters is quenched in structures consisting of ultrathin walls produced at high anodization voltages. The relaxation of photoconductivity in bulk InP substrates, porous layers, and utrathin membranes is investigated as a function of temperature and excitation power density. The obtained results suggest that PPC in porous InP layers is due to porosity induced potential barriers which hinder the recombination of photoexcited carriers, while the photoconductivity relaxation processes in ultrathin membranes are governed by surface states.
CRIS-Team Scopus Importer:2023-03-20